Maoism: an analysis of its development and relation to the national question - Mandić, Stefan (Sociološki pregled, 2025)
Most intellectual circles and political movements of the radical left, both traditional and modern, are mainly characterized by a negative, indifferent or instrumentalist attitude towards the nation and the national question. In contrast, Maoism showed greater willingness not to associate the consideration of changes and the revolution solely with the acting of the class, but also of the nation. In other words, Maoism did not hesitate to strive towards ideological radicalism and revolutionary principles, while simultaneously being national, and that is why it constitutes a specific form of the radical left that deserves a detailed scientific analysis. Therefore, the main aim of this paper is to determine the most important characteristics of the Maoist theory and ideology, the path of idea evolution within Maoism and the manner in which Maoism understands the nation. The first part of the paper contains the analysis of the historical context leading to the emergence of Maoism, followed by the history overview of the Chinese Communist Party, mainly during the period when it was led by Mao Tse-tung (Mao Zedong). The second part of the paper deals with the analysis of the basic characteristics of Maoism, its attitude towards the national question and its influence on other political movements.
Keywords: China; Maoism; nation; nationalism